Teenage pregnancy with catecholaminergic polymorphic ventricular tachycardia and documented ICD discharges - Ahmed, Aziez (Clin Case Rep, 2016)
We report the first case of pregnancy in a pediatric patient with catecholiminergic polymorphic ventricular tachycardia (CPVT). Pregnant adolescents with CPVT are at high risk for NSVT and malignant VT during pregnancy, despite antiarrhythmic medication. They may receive multiple implantable cardioverter defibrillator (ICD) therapies. Such patients require close monitoring with special care during the first trimester.